2020
DOI: 10.1186/s12955-020-01345-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the WHOQOL-BREF among next of kin to older persons in nursing homes

Abstract: Background: The worries of next of kin about their older loved ones in nursing homes can be extensive and can adversely affect their subjective experiences of their own physical, mental and social well-being. It is thus of utmost importance to measure the quality of life of next of kin in a valid and reliable way. Methods: The design is a cross-sectional study with psychometric evaluation based on classical test theory in preparation for a planned educational intervention study on palliative care. An abbreviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…It is hard to trust results based on a single question-it is possible to assess the general score, but not the one connected with a given dimension. The WHO-QOL questionnaire consists of four dimensions [54][55][56]. In those dimensions, free time is assessed in one question, and finance, family, and friend dimensions are assessed in two questions.…”
Section: Discussionmentioning
confidence: 99%
“…It is hard to trust results based on a single question-it is possible to assess the general score, but not the one connected with a given dimension. The WHO-QOL questionnaire consists of four dimensions [54][55][56]. In those dimensions, free time is assessed in one question, and finance, family, and friend dimensions are assessed in two questions.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation with standardized tools of the adaptation of the family member is practically absent in the literature. Only two studies have been found: one by Rosén et al [ 22 ] who evaluated quality of life using the World Health Organization’s quality-of-life self-assessment instrument (WHOQOL) in a sample of 254 family members in Sweden, and another work by Pérz-Dorado et al [ 23 ], who applied the “Zarit-caregiver burden scale” to a sample of 20 elderly relatives from a nursing home in Seville. However, quality of life is a broader concept than the adaptation of the family members, although they are interrelated and in the Spanish study with Zarit they found that, according to family members, there was no burden since the care for the elderly was in the hands of the nursing home staff; hence this questionnaire is of little use.…”
Section: Introductionmentioning
confidence: 99%
“…El cuestionario de Calidad de Vida de la Organización Mundial de la Salud en su versión corta (WHOQOL-BREF) fue desarrollado por el "WHOQOL Group" en el año de 1993, con la finalidad de medir la percepción de la persona, con o sin enfermedad, sobre su calidad de vida en general (global) y la satisfacción percibida en relación a su salud física, salud psicológica, relaciones sociales y el ambiente; su versión al español fue aprobada en el año de 1998, por el mismo grupo, su versión en sueco fue utilizada en una investigación con 254 familias de adultos mayores que viven en residencias, demostrando ser fiable 2675-5459 y con buena consistencia interna (Rosén, Ahlström & Lexén, 2020), existen otros estudios encontrados en versión pakistaní (Saquib-Lodhi et al, 2017), inglés, chino y malayo (Cheung et al, 2017), amárico (Reba, Birhane & Gutema, 2019), taiwanés (Lin et al, 2019). Para la validación del WHOQOL-BREF se aplicó la prueba a población en general, pacientes ambulatorios, pacientes con esquizofrenia y a sus cuidadores (Lucas, 1998); además, existen estudios que ilustran la validez del instrumento, aplicándolo a una muestra de 250 personas adultas mayores, quienes reflejaron satisfacción en las cuatro áreas específicas que mide la prueba, los resultados fueron: 62.72% para salud física, 62.78% para salud psicológica, 63.89% para relaciones interpersonales y 63.29% para el ambiente (Robles, 2017); en otro estudio, se evidenció una satisfacción global de 54.45% de los participantes y para el cálculo de las dimensiones se alcanzaron medias porcentuales de 39.32%, 42.67%, 39.30% y 37.40% respectivamente (Flores-Herrera et al, 2018).…”
Section: Introductionunclassified